Family intervention program for autism - Amira, Luqyana Dhiya; Wagino, Wagino; Budayasa, I Ketut; Yuliyati, Yuliyati (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Interventions can minimize the impact of developmental barriers on autism. Inconsistent interventions result in behavioral deterioration. Parents have a big role to provide consistent intervention to children. This study aims to review home intervention programs that family can do at home. The research method used is a literature review. The data collection method used is the literature related to home-based autism interventions and family intervention. The results of the study show several programs that can be applied by families at home. The results showed the intervention models that can be done by family are ABA, PLAY, dan TEACCH. Through this study, it can be concluded that ABA is the most effective technique that can be used as a basis for implementing family interventions. Comprehensive interventions are also highly recommended for home interventions, such as modifying the environment and providing preschool life skills.